2021
DOI: 10.3390/ijms22052376
|View full text |Cite
|
Sign up to set email alerts
|

RGDS-Modified Superporous Poly(2-Hydroxyethyl Methacrylate)-Based Scaffolds as 3D In Vitro Leukemia Model

Abstract: Superporous poly(2-hydroxyethyl methacrylate-co-2-aminoethyl methacrylate) (P(HEMA-AEMA)) hydrogel scaffolds are designed for in vitro 3D culturing of leukemic B cells. Hydrogel porosity, which influences cell functions and growth, is introduced by adding ammonium oxalate needle-like crystals in the polymerization mixture. To improve cell vitality, cell-adhesive Arg-Gly-Asp-Ser (RGDS) peptide is immobilized on the N-(γ-maleimidobutyryloxy)succinimide-activated P(HEMA-AEMA) hydrogels via reaction of SH with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…37 For example, Svozilová et al optimized a BM niche model of leukemia, recapitulating the trabecular bone structure using a hydrogel scaffold, using needle-shaped ammonium oxalate as a porogen. 43 Apoorva et al designed biomaterials-based hydrogels with tunable mechanical stiffness for B lymphoma growth, demonstrating that a lymphoid-like stiffness influences BCR expression levels in malignant cells, with consequences for proliferation and drug resistance. 44 Along with the possibility of tuning physical properties, matrices can also be functionalized with a wide variety of compounds to make them biologically active.…”
Section: Scaffold-based Modelsmentioning
confidence: 99%
“…37 For example, Svozilová et al optimized a BM niche model of leukemia, recapitulating the trabecular bone structure using a hydrogel scaffold, using needle-shaped ammonium oxalate as a porogen. 43 Apoorva et al designed biomaterials-based hydrogels with tunable mechanical stiffness for B lymphoma growth, demonstrating that a lymphoid-like stiffness influences BCR expression levels in malignant cells, with consequences for proliferation and drug resistance. 44 Along with the possibility of tuning physical properties, matrices can also be functionalized with a wide variety of compounds to make them biologically active.…”
Section: Scaffold-based Modelsmentioning
confidence: 99%
“…Recently, primary CLL cells were cultured in 3D-printed, commercially available CELLINK Bioink, which maintained 40% CLL-cell viability after one month [120]. It is tempting to speculate that adding CD40L and/or interleukins could improve these 3D models and also induce significant proliferation [121]. It has been shown that T-cell signals can be introduced to scaffolds via injection, the covalent linking of recombinant factors [122], or seeding with supportive cells producing the desired factors.…”
Section: In Vitro: Cll Co-cultures In 3dmentioning
confidence: 99%
“…4 Development of three-dimensional (3D) models that are able to accurately mimic the CLL microenvironment may help to bridge the gap between current in vitro systems and the physiologic CLL microenvironment in vivo, overcoming some of the current limitations of in vitro CLL studies. Recent efforts have been made toward the development of bone marrow-specific CLL models, 5,6 yet it is currently accepted that the LN is the critical site of CLL proliferation. 2 We attempted to establish a model that incorporates key aspects of CLL LN biology, taking into account physiological relevance.…”
Section: Introductionmentioning
confidence: 99%